50.7k views
3 votes
Solve the following: - (5x +7) + 1= -5x - 5

2 Answers

2 votes

Answer:

There is NO SOLUTION for x.

Explanation:

Firstly, you have to expand it, leaving no brackets in the expression :

-(5x + 7) + 1 = -5x - 5

-5x - 7 + 1 = -5x - 5

Next, you have to move all the same variables to one side and solve :

-5x - 7 + 1 = -5x - 5

-5x -6 = -5x - 5

-5x + 5x = -5 + 6

0x = 1

0 = 1 (UNDEFINED)

User Stefan Sullivan
by
4.9k points
4 votes

Answer:

No solutions

Explanation:

Distribute the -1 on the left side

-1(5x+7) +1 = -5x-5

-1*5x +-1*7 +1 = -5x -5

-5x-7+1=-5x-5

Combine like terms

-5x-6=-5x-5

Add 5x on both sides

-6=-5

This statement is false, therefore there are no solutions

Hope this helps! :)

User Akuzminsky
by
4.5k points